2019
DOI: 10.1186/s12870-019-2157-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TCP8 delays Arabidopsis flowering through a FLOWERING LOCUS C-dependent pathway

Abstract: Background: Flowering is a key process in the life cycle of plants. The transition from vegetative to reproductive growth is thus under sophisticated regulation by endogenous and environmental signals. The plant-specific Teosinte Branched 1/Cycloidea/Proliferating Cell Factors (TCP) family transcription factors are involved in many biological processes, but their roles in regulating flowering have not been totally elucidated. Results: We explored the role of Arabidopsis TCP8 in plant development and, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…As described above, TCP8, which plays a role in plant-pathogen interactions [ 180 ] and flowering control [ 181 ], contains several IDRs. Of those, the C-terminal IDR contains the AD ( Figure 1 F).…”
Section: Id and Dynamics Of Tf-based Interactionsmentioning
confidence: 99%
“…As described above, TCP8, which plays a role in plant-pathogen interactions [ 180 ] and flowering control [ 181 ], contains several IDRs. Of those, the C-terminal IDR contains the AD ( Figure 1 F).…”
Section: Id and Dynamics Of Tf-based Interactionsmentioning
confidence: 99%
“…TCP and their homologs are regulated by the conserved microRNA miR319 in different species. The miR319-regulated TCPs are involved in regulating the leaf morphogenesis [ 13 ], flower architecture [ 14 ], hormone biosynthesis and response [ 15 ]. In Arabidopsis , AtTCP2-4 , AtTCP10 , and AtTCP24 are belong to the CIN family members which contain miR319 binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Teosinte branched1, cycloidea, and proliferating cell factors (TCPs), belonging to the bHLH transcription factor family, are widely involved in leaf morphology regulation (Aggarwal et al, 2010;Zhao M. L. et al, 2020;Lan et al, 2021). Previous studies have confirmed that TCP transcription factors widely participate in the regulation of flower shape, leaf shape, and stem and root development and have been identified in many plant species (Wang et al, 2019;He J. et al, 2020;Wen et al, 2020). Leaf shape in the Aceraceae family differs among different species, showing different variations, such as trifoliate, pinnate and lobed leaves.…”
Section: The Genes Related To Leaf Color Changementioning
confidence: 99%